Spectroscopic investigations on γ-irradiated Eu3+ and Dy3+ doped oxyfluoride glasses. (March 2015) - Sharma, G.; Bagga, R.; Cemmi, A.; Falconieri, M.; Baccaro, S.
Abstract: Changes in the UV–visible spectra of undoped and Dy/Eu singly doped oxyfluoride glasses with varying PbF2 /CdF2 content were studied under high doses of gamma irradiation. The unirradiated undoped and doped glasses exhibited strong UV absorption and characteristic absorption bands due to the presence of rare earth ions. Gamma irradiation caused loss of transmission and red shift in the cut-off wavelength for the undoped and doped samples. The radiation induced absorption coefficient and energy band gap depicted variation due to the nature of rare earth as well as the host matrix. The rare earth addition affected the physical properties (density, refractive index, molar volume) and the structure of the studied glasses revealed by Fourier Transform Infrared Spectroscopy. Highlights: Gamma irradiation of oxyfluoride glasses. Eu-doped glasses more radiation durable than Dy-doped glasses. Dependence of tramittance on CdF2 /PbF2 ratio.